Measurement of Nuclear Lifetimes and B(E2) Values in 130Xe as a Test for E(5) Symmetry - Konstantinopoulos, T.; al., et (HNPS Advances in Nuclear Physics, 2020)
As a continuation of the previous measurement in 128Xe [1], [2], [3], another E(5) candidate, 130Xe, has been studied through the novel experimental technique Coulex-plunger in inverse kinematics. The measurements have been undertaken at the JYFL accelerator facility in Jyvaskyl ̈a, Finland. For the purpose of this experiment the Cologne plunger was coupled to the JYFL cyclotron which delivered the 130Xe beam. Excited states in 130Xe were populated by the natFe(130Xe, 130Xe*) reaction at E(130Xe)=500 MeV and the subsequent de-excitations were detected in the JUROGAM γ-ray array. By applying the well known Differential Decay Curve Method (DDCM) [4], lifetimes of the 2^+_1 and 4^+_1 excited states were determined. In addition, since the investigated nucleus is excited through the Coulomb interaction, it is possible to perform a full Coulomb excitation analysis of the data using the computer code GOSIA [5] which will allow the determination of B(E2) values of the transitions up to the 6^+_1 excited state.